Risk Management, the Subprime Crisis and Financialisation: The Role of Risk Management in the Generation and Transmission of the Subprime Crisis - Lagoa, S.; Leão, E.; Barradas, R. (FESSUD Working Paper Series Nº37, 2014)
Over time the financial sector has gained greater relevance in the economy, a phenomenon that some call financialisation. Contrary to the mainstream view, financialisation literature emphasises that risk management by financial corporations will not be socially efficient in a context of deregulated markets and will ultimately lead to an increase of aggregate risk and crises. To assess the validity of such claim, in this paper we review the literature on risk management during the Subprime crisis. These failures fall into three categories: technique and methodology, corporate governance and strategy, and regulation and external factors. These failures can be interpreted in the light of the financialisation perspective, which is therefore a valuable approach when addressing regulatory changes in the financial system.